Beach Litter as Public Pedagogy: Moral Learning, Environmental Character Formation, and Thoreau’s Ecological Thought - I Putu Raditya Arya Bagus Pinatih; I Gede Saman (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
Beach litter is not only a visible waste problem but also a pedagogical and moral issue that reflects how people learn to relate to coastal environments in public space. This article examines the causes and consequences of beach litter through Henry David Thoreau’s ecological thought, public pedagogy, moral learning, and environmental character formation. Using a theory-informed qualitative literature review, the study synthesizes peer-reviewed journal articles, academic books, and selected policy-oriented publications on marine litter, pro-environmental behavior, environmental education, and sustainability pedagogy. The review shows that beach litter is driven by convenience-seeking behavior, weak social norms, inadequate waste infrastructure, limited ecological awareness, and a broader culture of disposable consumption. It also finds that beaches function as informal pedagogical spaces where conduct is modeled, observed, and socially normalized. Thoreau’s emphasis on simplicity, attentiveness, moral restraint, and respectful coexistence with nature provides an ethical lens for interpreting these dynamics. The article argues that lasting change requires more than awareness alone. Effective responses must integrate experiential education, visible stewardship, supportive infrastructure, community participation, and value-oriented public communication to strengthen environmental responsibility and ecological character.